First report of Pectobacterium aroidearum causing bacterial soft rot of carrot in Taiwan - Tang, Wen-Qian (Plant disease, 2020)
Carrot (Daucus carota) is an important root vegetable planted and consumed worldwide (Stein and Nothnagel 1995). In June 2020, carrots (cv. New Kuroda) showing soft rot symptoms were observed in a 600 sqft plot located in Pitou, Changhua, Taiwan (23°54'00.9"N, 120°28'37.3"E; with around 400 plants). About 10% of the plants on site had similar symptoms; infected taproot tissues were macerated (Figure S1) and emitted a foul odor. In most cases, the peels above the rotten tissues remain intact. Two infected plants were brought to the lab. Macerated tissues were suspended in water and examined under a microscope at 600X (without staining). Rod, motile bacteria were observed in all of the samples and the bacteria were isolated onto nutrient agar. Three bacterial strains were obtained from two taproots; strain Car1 was isolated from one plant, and strains Car2 and Car3 were isolated from the other. Their colonies were translucent, round and convex. All isolates could ferment glucose and induce soft rot symptoms on potato tuber slices (Schaad et al. 2001). They were not able to produce indigoidine on yeast dextrose calcium carbonate agar and were tested negative for phosphatase activity (Schaad et al. 2001). The 16S rDNA of Car1 to Car3 were amplified using primers 27F/1492R (Lane 1991). Cloning and sequencing of their 16S rDNA (GenBank accession no. MT889640) revealed that their sequences shared 99.9% identity (1,463/1,464 bp) with that of Pectobacterium aroidearum CFBP 8168T (SCRI 109T; GenBank accession no. NR_159926.1). Multilocus sequence analyses targeting the three isolates' dnaX, leuS and recA genes were conducted. The concatenated sequences (1,596 bp) of Car1 to Car3 and those included in a previous work (Portier et al. 2019) were subjected to phylogenetic analysis. The sequences of Car1 to Car3 were identical (GenBank accession nos. MT892671-MT892673). A maximum-likelihood tree showed that the three isolates belonged to the same clade as P. aroidearum CFBP 8168T (GenBank accession nos. MK516971, MK517115 and MK517259; Figure S2). For the concatenated sequences analyzed, the identity between P. aroidearum CFBP 8168T and our three isolates was 99.4% (1,587/1,596 bp). The pathogenicity of these isolates was determined by inoculating the bacteria into carrot (cv. Xiangyang No.2) taproots. Strains Car1 to Car3 were grown on NA for 48 h (28 °C) and cell suspensions with OD600 values of 0.3 (2.4 x 108 CFU/ml; in water) were prepared. The suspensions of each strain (100 μl) were loaded into 200 μl pipette tips. The tips were then pierced into intact carrot taproots (2.4 cm deep), ejected and left on the plants (one tip per plant). Three taproots were tested for each strain. Tips loaded with 100 μl of water were used for the controls (three replicates). The plants were incubated in a sealed plastic container kept in a growth chamber set at 28°C. After 48 h, all of the inoculated taproots produced soft rot symptoms resembling those observed in the field and plants in the control group did not. Bacteria were re-isolated from macerated tissues of the artificially infected plants and found to share the same leuS sequence with Car1 to Car3. Occurrences of carrot soft rot in Taiwan have only been attributed to Dickeya spp. (Erwinia chrysanthemi) in previous studies (Hsu and Tzeng 1981). The present study is the first report of P. aroidearum infecting carrots in Taiwan. The findings may add to our understanding of the diversity of soft rot pathogens affecting carrot production in Taiwan